Tropospheric ozone effects on chemical composition and decomposition rate of Quercus ilex L. leaves. - Baldantoni, Daniela; Fagnano, Massimo; Alfani, Anna (The Science of the total environment, 2011)
We determined the effects of tropospheric ozone on the chemical composition of Quercus ilex L. leaves and their decomposition, with a view to assessing the influence of ozone on nutrient cycling and the sustainability of Mediterranean holm oak forests. Forming one of the most widespread thermophilous vegetation communities in the area, Q. ilex is a dominant and widespread evergreen oak in the Mediterranean, where concentrations of tropospheric ozone are particularly high. The dynamics of carbon, nitrogen, lignin and cellulose concentrations were monitored for six months during the decomposition of leaves from plants subjected to controlled ozone exposure in open-top chambers. Ozone-exposed leaves, compared to unexposed leaves, showed no significant differences in C, N, lignin and cellulose concentrations prior to the incubation in mesocosms. However, during decomposition, leaves from plants exposed to ozone lost C significantly more slowly and showed a higher C/N ratio than unexposed leaves. Ozone exposure significantly slowed down the decomposition rate, indicating a negative effect of tropospheric ozone on nutrient cycling, which may reduce long-term sustainability of the holm oak forest.
Keywords: Air Pollutants; Air Pollutants: chemistry; Air Pollutants: metabolism; Air Pollutants: toxicity; Atmosphere; Atmosphere: chemistry; Carbon; carbon cycle; Carbon: analysis; Carbon: metabolism; Cellulose; Cellulose: analysis; Cellulose: metabolism; Decaying leaf composition; Holm oak leaves; Lignin; Lignin: analysis; Lignin: metabolism; Mediterranean area; nitrogen; nitrogen cycle; Nitrogen: analysis; Nitrogen: metabolism; Ozone; ozone exposure; Ozone: chemistry; Ozone: metabolism; Ozone: toxicity; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: metabolism; Quercus; Quercus: chemistry; Quercus: metabolism

Vegetation response to obliquity and precession forcing during the Mid-Pleistocene Transition in Western Mediterranean region (ODP site 976) - Joannin, Sébastien; Bassinot, Franck; Nebout, Nathalie Combourieu; Peyron, Odile; Beaudouin, Célia (Quaternary Science Reviews, 2011)
The ODP leg 161 Site 976 (Alboran Sea) is a deep-sea section sampled at a water depth of 1108 m in the Western Mediterranean Sea. Pollen analysis provides a vegetation and climate record of the Mid Pleistocene Transition (MPT), roughly one million years ago. The age-model tied to biostratigraphic events was revised by aligning the pollen climate index (PCI) to Mediterranean (KC01b) and global (LR04) oxygen isotope records. The studied time slice spans the interval w1.09 Ma (MIS 31) to w0.90 Ma (MIS 23). Across this interval, past phytogeography of nowadays extinct taxa, which were rare, allows a successful application of the modern analogues technique (MAT) to quantitative climate reconstructions for the MPT. Five, long-term, obliquity-related vegetation successions (O1 to O5), and eight short-term, precessionrelated vegetation successions (P1 to P8) are observed within the studied interval. These vegetation successions, regardless of their duration, show the same pattern: the progressive replacement of temperate trees by mountainous taxa, and then by herbs and steppe maxima. Precession-related successions correspond, therefore, to as dramatic vegetation changes as those driven by obliquity, including a ﬁnal steppe phase under deteriorated climate conditions. Wavelet analysis of the PCI record shows that the Western Mediterranean experienced a shift at 1.01 Ma from precession-dominated frequencies (1.05e1.01 Ma) to obliquity-dominated frequencies (1.01e0.9 Ma). There is, therefore, an apparent discrepancy between wavelet analysis results and vegetation dynamic analysis (which suggests that obliquity and precession are recorded throughout the entire studied interval). This discrepancy could result from the fact that the PCI record sums, somehow, similar vegetation changes (wet to dry) occurring at different periodicities. Such a complex vegetation dynamics is mathematically rendered through a single parameter (i.e. principal component), which does not successfully catch the subtle combinations of variability occurring at two close periodicities. Furthermore, the pollen-inferred Early Pleistocene vegetation dynamic (and climate) of the Western Mediterranean region does not show a decrease of the obliquity response relative to the precession response at the onset of the MPT
Keywords: climate changes; Mediterranean area; obliquity; Pleistocene (voyant); Pollen analysis; Precession; vegetation successions

Holocene circum-Mediterranean vegetation changes: Climate forcing and human impact - Jalut, Guy; Dedoubat, Jean Jacques; Fontugne, Michel; Otto, Thierry (Quaternary International, 2009)
The Mediterranean climate and its variability depend on global-scale climate patterns. Close correlations appear when comparing Holocene palaeoenvironmental data (lake levels, ﬂuvial activity, Mediterranean surface temperature and salinity, marine sedimentation) with the main stages of the history of the circum-Mediterranean vegetation. They indicate an evolution of the Mediterranean biome controlled by the climate and emphasize the teleconnections between the climate of the Mediterranean area and the global climatic system. In the circum-Mediterranean area, the Holocene can be divided into three periods: a lower humid Holocene (11 500–7000 cal BP) interrupted by dry episodes; a transition phase (7000–5500 cal BP) during which occurred a decrease in insolation as well as the installation of the present atmosphere circulation in the northern hemisphere; and an upper Holocene (5500 cal BP—present) characterized by an aridiﬁcation process. Throughout the Holocene, humans used and modiﬁed more or less strongly the environment but the climatic changes were the determining factors of the evolution of the Mediterranean biome. Societies had to adapt to natural environmental variations, their impact on the environment increasing the ecological consequences of the global changes.
Keywords: climate; climatic changes; Holocene; Mediterranean area; pollen data; vegetation dynamics (voyant)

Holocene circum-Mediterranean vegetation changes: Climate forcing and human impact - Jalut, Guy; Dedoubat, Jean Jacques; Fontugne, Michel; Otto, Thierry (Quaternary International, 2009)
The Mediterranean climate and its variability depend on global-scale climate patterns. Close correlations appear when comparing Holocene palaeoenvironmental data (lake levels, ﬂuvial activity, Mediterranean surface temperature and salinity, marine sedimentation) with the main stages of the history of the circum-Mediterranean vegetation. They indicate an evolution of the Mediterranean biome controlled by the climate and emphasize the teleconnections between the climate of the Mediterranean area and the global climatic system. In the circum-Mediterranean area, the Holocene can be divided into three periods: a lower humid Holocene (11 500–7000 cal BP) interrupted by dry episodes; a transition phase (7000–5500 cal BP) during which occurred a decrease in insolation as well as the installation of the present atmosphere circulation in the northern hemisphere; and an upper Holocene (5500 cal BP—present) characterized by an aridiﬁcation process. Throughout the Holocene, humans used and modiﬁed more or less strongly the environment but the climatic changes were the determining factors of the evolution of the Mediterranean biome. Societies had to adapt to natural environmental variations, their impact on the environment increasing the ecological consequences of the global changes.
Keywords: climate; climatic changes; Holocene; Mediterranean area; pollen data; vegetation dynamics (voyant)

Estimating red deer abundance in a wide range of management situations in Mediterranean habitats - Acevedo, P; Ruiz-Fons, F; Vicente, J; Reyes-García, a. R; Alzaga, V; Gortázar, C (Journal of Zoology, 2008)
When human interventions interfere with the natural regulation of wildlife populations by favouring some species, overabundance can emerge. We evaluated different methods of estimating red deer abundance in a wide range of population densities from southern Spain. Distance sampling estimates were used as the reference method across 22 localities and were compared with two kilometric abundance indices (KAIs), four indices based on pellet group counts and two browsing indices (BWIs). The average red deer density estimated by distance sampling was 19.51 3.19 deer per 100 ha, showing a wide range across the study area (0.04–66.77). Distance sampling estimates correlated with the KAIs, pellet group-based index and the BWI. The agreement with distance sampling improved when groups were used instead of individuals in the KAIs, when the minimum pellet group size was ﬁxed at 20 pellets in the dropping counts, and when only highly palatable species were used in the BWI. Thus, several direct and indirect methods can estimate red deer abundance in Mediterranean habitats from Southern Spain with appropriate modiﬁcations.
Keywords: deer management; direct and indirect methods; Mediterranean area; overabundance; population abundance; red deer; ungulates

Estimating red deer abundance in a wide range of management situations in Mediterranean habitats - Acevedo, P.; Ruiz-Fons, F.; Vicente, J.; Reyes-García, a R.; Alzaga, V.; Gortázar, C. (Journal of Zoology, 2008)
When human interventions interfere with the natural regulation of wildlife populations by favouring some species, overabundance can emerge. We evaluated different methods of estimating red deer abundance in a wide range of population densities from southern Spain. Distance sampling estimates were used as the reference method across 22 localities and were compared with two kilometric abundance indices (KAIs), four indices based on pellet group counts and two browsing indices (BWIs). The average red deer density estimated by distance sampling was 19.51 3.19 deer per 100 ha, showing a wide range across the study area (0.04–66.77). Distance sampling estimates correlated with the KAIs, pellet group-based index and the BWI. The agreement with distance sampling improved when groups were used instead of individuals in the KAIs, when the minimum pellet group size was ﬁxed at 20 pellets in the dropping counts, and when only highly palatable species were used in the BWI. Thus, several direct and indirect methods can estimate red deer abundance in Mediterranean habitats from Southern Spain with appropriate modiﬁcations.
Keywords: deer management; direct and indirect methods; Mediterranean area; overabundance; population abundance; red deer; ungulates

Estimation of Mediterranean forest transpiration and photosynthesis through the use of an ecosystem simulation model driven by remotely sensed data - Anselmi, Silvia; Chiesi, Marta; Giannini, Monica; Manes, Fausto; Maselli, Fabio (Global Ecology and Biogeography, 2004)
Aim This paper investigates the use of an ecosystem simulation model, FOREST-BGC, to estimate the main ecophysiological processes (transpiration and photosynthesis) of Mediterranean coastal forest areas using remotely sensed data. Location Model testing was carried out at two protected forest sites in central Italy, one of which was covered by Turkey oak (Circeo National Park) and the other by holm-oak (Castelporziano Estate). Methods At both sites, transpiration and photosynthesis measurements were collected in the field during the growing seasons over a four-year period (1999 and 2001 for the Turkey oak; 1997, 1999 and 2000 for the holm-oak). Calibration of the model was obtained through combining information derived from ground measurements and remotely sensed data. In particular, remote sensing estimates of the Leaf Area Index derived from 1 × 1-km NOAA AVHRR Normalized Difference Vegetation Index data were used to improve the adaptation of the model to local forest conditions. Results The results indicated different strategies regarding water use efficiency, ‘water spending’ for Turkey oak and ‘water saving’ for holm-oak. The water use efficiency for the holm-oak was consistently higher than that for the Turkey oak and the relationship between VPD and WUE for the holm-oak showed a higher coefficient of determination (R2 = 0.9238). Comparisons made between the field measurements of transpiration and photosynthesis and the model estimates showed that the integration procedure used for the deciduous oak forest was effective, but that there is a need for further studies regarding the sclerophyllous evergreen forest. In particular, for Turkey oak the simulations of transpiration yielded very good results, with errors lower than 0.3 mm H2O/day, while the simulation accuracy for photosynthesis was lower. In the case of holm-oak, transpiration was markedly overestimated for all days considered, while the simulations of photosynthesis were very accurate. Main conclusions Overall, the approach offers interesting operational possibilities for the monitoring of Mediterranean forest ecosystems, particularly in view of the availability of new satellite sensors with a higher spatial and temporal resolution, which have been launched in recent years.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: AVHRR; Ecosystem; FOREST-BGC; Mediterranean area; Modelling; photosynthesis; Quercus cerris; Quercus ilex; Transpiration; water efficiency

Estimation of Mediterranean forest transpiration and photosynthesis through the use of an ecosystem simulation model driven by remotely sensed data - Anselmi, Silvia; Chiesi, Marta; Giannini, Monica; Manes, Fausto; Maselli, Fabio (Global Ecology and Biogeography, 2004)
Aim This paper investigates the use of an ecosystem simulation model, FOREST-BGC, to estimate the main ecophysiological processes (transpiration and photosynthesis) of Mediterranean coastal forest areas using remotely sensed data. Location Model testing was carried out at two protected forest sites in central Italy, one of which was covered by Turkey oak (Circeo National Park) and the other by holm-oak (Castelporziano Estate). Methods At both sites, transpiration and photosynthesis measurements were collected in the field during the growing seasons over a four-year period (1999 and 2001 for the Turkey oak; 1997, 1999 and 2000 for the holm-oak). Calibration of the model was obtained through combining information derived from ground measurements and remotely sensed data. In particular, remote sensing estimates of the Leaf Area Index derived from 1 × 1-km NOAA AVHRR Normalized Difference Vegetation Index data were used to improve the adaptation of the model to local forest conditions. Results The results indicated different strategies regarding water use efficiency, ‘water spending’ for Turkey oak and ‘water saving’ for holm-oak. The water use efficiency for the holm-oak was consistently higher than that for the Turkey oak and the relationship between VPD and WUE for the holm-oak showed a higher coefficient of determination (R2 = 0.9238). Comparisons made between the field measurements of transpiration and photosynthesis and the model estimates showed that the integration procedure used for the deciduous oak forest was effective, but that there is a need for further studies regarding the sclerophyllous evergreen forest. In particular, for Turkey oak the simulations of transpiration yielded very good results, with errors lower than 0.3 mm H2O/day, while the simulation accuracy for photosynthesis was lower. In the case of holm-oak, transpiration was markedly overestimated for all days considered, while the simulations of photosynthesis were very accurate. Main conclusions Overall, the approach offers interesting operational possibilities for the monitoring of Mediterranean forest ecosystems, particularly in view of the availability of new satellite sensors with a higher spatial and temporal resolution, which have been launched in recent years.
Keywords: AVHRR; Ecosystem; FOREST-BGC; Mediterranean area; Modelling; photosynthesis; Quercus cerris; Quercus ilex; Transpiration; water efficiency

Evaluation of goat milk and cheese qualities and the influence of the livestock production system in the Mediterranean - Goby, J P; Rochon, J J (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
The herds of dairy goats using marginal areas of the French Mediterranean region have a double objective: milk production and maintenance of the natural environment in areas prone to fires. The association of rearing techniques adapted to the conservation of the natural environment and to quality milk production is a key factor in the survival of the systems. In the Eastern Pyrenees, milk quality in two goat systems is studied. A rangeland-based system: situated at the piedemont of the Alberes Massif, the site integrates a cork oak grove with a maquis-type cover of Erica arborea. The herd grazes in the maquis and also feed on hay and concentrate. A system based on forage: situated on the plains, the herd is fed in the stable. The first results of the rangeland system show a large evolution of the butyric acid levels and and inversion of these levels in the summer. Judging from the selection made by the goats, the supply of nutrients on the rangeland is less rich in fibre than the composition of shrubs would lead us to think.
Keywords: cheese; Goat; Mediterranean area; milk; Quality

An overview of the Castelporziano experiments - Seufert, G; Bartzis, J; Bomboi, T; Ciccioli, P; Cieslik, S; Dlugi, R; Foster, P; Hewitt, C N; Kesselmeier, J; Kotzias, D; Lenz, R; Manes, F; et al. (Atmospheric Environment, 1997)
This paper reviews the major outcomes of the measuring campaigns performed at the Castelporziano nature preserve near Rome, Italy, by 14 European laboratories as part of the BEMA (Biogenic Emissions in the Mediterranean Area)-project. Six campaigns of 1–4 weeks duration were carried out in different seasons of the years 1993–1994 at semi-continuously running test plots in the nature reserve, representing common Mediterranean vegetation types. The aim was to characterise, at the different test plots, the atmospheric chemical and meteorological situations, the plant biomass and physiology, the type, amount and controls of emissions from different plants by means of branch enclosures, and the BVOC emission fluxes from different ecosystems, by scaling up enclosure data from individual sources, and by measuring fluxes directly by use of micrometeorological methods. An important focus during the initial phase of the five year BEMA-project was the harmonisation and improvement of the analytical, physiological and micrometeorological methods used, and the development and testing of new methods for measuring BVOC fluxes.
Keywords: air chemistry; Biogenic emission; ecophysiology; Mediterranean area; micrometeorology; Vegetation

The terpenoid emission pattern of Quercus coccifera L coincides with the emission pattern found with Quercus ilex L - Hansen, U; Seufert, G (PROCEEDINGS OF EUROTRAC SYMPOSIUM `96 - TRANSPORT AND TRANSFORMATION OF POLLUTANTS IN THE TROPOSPHERE, VOL 2: EMISSIONS, DEPOSITION, LABORATORY WORK AND INSTRUMENTATION, 1997)
Monoterpene and isoprene emission rates from Kermes or Holly oak (Quercus coccifera L.), an evergreen shrub or small tree which is widely present in the Mediterranean area, were investigated in a greenhouse using a dynamic enclosure technique, Monoterpenes emitted with the highest rates from Quercus coccifera were alpha-pinene, sabinene and beta-pinene. alpha-pinene contributed 41 % to the total monoterpene emission, sabinene 28 % and beta-pinene 25 %. The isoprene emission rate was 0.7 % of the total monoterpene emission rate. Standardisation to 30 degrees C revealed a total monoterpene emission rate of 18.7 mu g gLDW(-1) h(-1). The data show that terpenoid emissions from Kermes oak (Quercus coccifera L.) are qualitatively and quantitatively similar to those of Helm oak (Quercus ilex L.). Both species have to be considered as strong monoterpene emitters, Emissions are considerably higher compared to the emission factor of 1.2 mu g C gLDW(-1) h(-1) which was assumed to represent the monoterpene emission rate from Mediterranean ecosystems at standard conditions in a study about a global model of natural VOC emissions.
Keywords: alpha-pinene; beta-pinene; isoterpene; Mediterranean area; Monoterpene; Quercus coccifera L.; sabinene; terpenoid; VOC emissions

The terpenoid emission pattern of Quercus coccifera L coincides with the emission pattern found with Quercus ilex L - Hansen, U.; Seufert, G. (PROCEEDINGS OF EUROTRAC SYMPOSIUM `96 - TRANSPORT AND TRANSFORMATION OF POLLUTANTS IN THE TROPOSPHERE, VOL 2: EMISSIONS, DEPOSITION, LABORATORY WORK AND INSTRUMENTATION, 1997)
Monoterpene and isoprene emission rates from Kermes or Holly oak (Quercus coccifera L.), an evergreen shrub or small tree which is widely present in the Mediterranean area, were investigated in a greenhouse using a dynamic enclosure technique, Monoterpenes emitted with the highest rates from Quercus coccifera were alpha-pinene, sabinene and beta-pinene. alpha-pinene contributed 41 % to the total monoterpene emission, sabinene 28 % and beta-pinene 25 %. The isoprene emission rate was 0.7 % of the total monoterpene emission rate. Standardisation to 30 degrees C revealed a total monoterpene emission rate of 18.7 mu g gLDW(-1) h(-1). The data show that terpenoid emissions from Kermes oak (Quercus coccifera L.) are qualitatively and quantitatively similar to those of Helm oak (Quercus ilex L.). Both species have to be considered as strong monoterpene emitters, Emissions are considerably higher compared to the emission factor of 1.2 mu g C gLDW(-1) h(-1) which was assumed to represent the monoterpene emission rate from Mediterranean ecosystems at standard conditions in a study about a global model of natural VOC emissions.
The following values have no corresponding Zotero field: periodical: PROCEEDINGS OF EUROTRAC SYMPOSIUM `96 - TRANSPORT AND TRANSFORMATION OF POLLUTANTS IN THE TROPOSPHERE, VOL 2: EMISSIONS, DEPOSITION, LABORATORY WORK AND INSTRUMENTATION pub-location: ASHURST LODGE, SOUTHAMPTON, HANTS, ENGLAND S04 2AA
Keywords: alpha-pinene; beta-pinene; isoterpene; Mediterranean area; Monoterpene; Quercus coccifera L.; sabinene; terpenoid; VOC emissions